Strengthening Social Piety Values through Academic Studies with Bibliometric Analysis of Research Publications 2015-2025 - Ali Anhar Syi'bul Huda; Aghnia Aghnia; Abid Nurhuda; Hamdi Hamdi; Walid In'am Ahmad; Dena Sri Anugerah; Sri Sutrianti (Faculty of Teacher Training and Education, Palangka Raya University, Central Kalimantan, Indonesia. Pos Code 73112, 2025)
This research is motivated by the idea that social piety values should reflect religious behavior that fosters concern, justice, and social responsibility. However, in practice, reality shows a decline in empathy, increasing individualism, and a decline in public moral role models. The purpose of this study is to examine the development of research on social piety during 2015–2025 and provide recommendations for strengthening these values through academic studies based on bibliometric analysis. The study used a quantitative design with a research bibliometric method. The primary data consisted of 744 article publications (clean data) from Crossref, while the secondary data consisted of books, proceedings, research reports, papers, and theses. Data analysis was conducted descriptively and qualitatively with the help of the Publish or Perish and VOSviewer applications. The study was conducted in October 2025. The results showed a significant increase in publications on the theme of social piety with a peak in 2024. The publication sources were dominated by journals (661 sources), followed by repositories, proceedings, digital books, and final project scientific papers. The nine most productive researchers are Muslim Sabarisman, Suradi, Kadaruddin Aiyub, Dinie Anggraeni Dewi, Habibullah, Nunik Hariyani, Ruaida Murni, Heri Harjanto Setiawan, and Muhammad Yasin. Developed issues include action, social interaction, Pancasila, schools, methods, and technology, while potential issues for development include communication, public, tradition, and teaching. The limitations of this research lie in the data source, which only uses Crossref and limited analytical tools, so it is recommended that further research combine the Scopus or WoS databases with advanced bibliometric tools.